Effects of an Interchain Disulfide Bond on Tropomyosin Structure: A Molecular Dynamics Study - Koubassova, Natalia A. (Int J Mol Sci, 2018)
Tropomyosin (Tpm) is a coiled-coil actin-binding dimer protein that participates in the regulation of muscle contraction. Both Tpm chains contain Cys190 residues which are normally in the reduced state, but form an interchain disulfide bond in failing heart. Changes in structural and functional properties of Tpm and its complexes with actin upon disulfide cross-linking were studied using various experimental methods. To understand the molecular mechanism underlying these changes and to reveal the possible mechanism of the involvement of the cross-linking in heart failure, molecular dynamics (MD) simulations of the middle part of Tpm were performed in cross-linked and reduced states. The cross-linking increased bending stiffness of Tpm assessed from MD trajectories at 27 °C in agreement with previous experimental observations. However, at 40 °C, the cross-linking caused a decrease in Tpm stiffness and a significant reduction in the number of main chain hydrogen bonds in the vicinity of residues 133 and 134. These data are in line with observations showing enhanced thermal unfolding of the least stable part of Tpm at 30–40 °C and accelerated trypsin cleavage at residue 133 at 40 °C (but not at 27 °C) upon cross-linking. These results allow us to speculate about the possible mechanism of involvement of Tpm cross-linking to heart failure pathogenesis.